Perencanaan Material Recovery Facility (MRF) Sampah: Studi Kasus Kelurahan Pulau Untung Jawa - Basransyah Basran; Riza Hudayarizka Riza (COMPACT: Spatial Development Journal, 2023)
Pulau Untung Jawa Village is one of the districts in the Kepulauan Seribu Regency, DKI Jakarta. The amount of managed waste in the Pulau Untung Jawa Village is only 30%, while the percentage of the unmanaged waste is 70%. The less optimal waste management in the Pulau Untung Jawa Village is due to limited waste processing facilities and the lack of waste recycling activities which are limited to collecting plastic waste with economic value and then selling it to garbage collectors. If not properly managed, garbage can become a serious problem for preserving the surrounding environment. One of the efforts that can be made to optimize waste recycling is by having a Temporary Waste Storage facility based on the Material Recovery Facility (MRF). This research aims to study waste generation's amount and composition and calculate the MRF land area planning. Waste generation in the Untung Jawa Village Island is 14.1 m3/day with a waste density of 180 kg/m3. The composition of the measured waste is organic 54.21%, paper 1.28%, rubber 2.12%, plastic 14.64%, glass 0.91%, cloth 2.41%, metal 0.37%, nappies 2, 71%, Styrofoam 2.96%, wood 10.12%, B3 waste 0.02% and other types of waste 8.24%. The total MFR land requirement in the planning year is 286.3 m2. With the MRF, the amount of waste that can be recycled in the planning year is 64.96% of the total waste generated, or the equivalent of 1.65 tons/day, with a residual waste of 0.89 tons/day.